Person Job Fit dan Komitmen Karir: Peran Keterlibatan Kerja - Noerchoidah, Noerchoidah; Ariprabowo, Tri; Nurdina, Nurdina; Alfia, Nida (UMSurabaya Publishing, 2023)
ABSTRACTOrganizations try to determine individuals who match their values and goals. This study explores a person's job fit's impact on career commitment by mediating work involvement. Data collection was carried out through a structured questionnaire. The population consists of lecturers working in Surabaya's private higher education sector. Determination of the sample using purposive sampling with a total of 158 respondents. Questionnaires that have been collected and tabulated were analyzed using PLS. The results reveal that personal job fit positively and significantly affects work involvement and career commitment. Work involvement has a positive and significant effect on career commitment. Work involvement mediates the relationship between personal job fit and career commitment. This research has implications for all institutions that wish to improve their employees' person–organizational fit and commitment. This implication helps institutions to take special initiatives to increase personal job fit for their lecturers, which in turn will increase the level of commitment of their lecturers to remain in their institutions.ABSTRAKOrganisasi mencoba menentukan individu yang sesuai dengan nilai dan tujuannya. Penelitian ini memiliki tujuan untuk mengeksplorasi dampak person job fit pada komitmen karir dengan mediasi keterlibatan kerja. Pengumpulan data dilakukan melalui kuesioner terstruktur. Populasi terdiri dari para dosen yang bekerja di sektor pendidikan tinggi swasta di Surabaya. Penentuan sampel menggunakan purposive sampling dengan jumlah 158 responden. Kuesioner yang telah terkumpul dan ditabulasikan dianalisis menggunakan PLS. Hasilnya mengungkapkan bahwa personal job fit berpengaruh positif dan signifikan terhadap keterlibatan kerja dan komitmen karir. Keterlibatan kerja berpengaruh positif dan signifikan terhadap komitmen karir. Keterlibatan kerja memediasi hubungan antara personal job fit dan komitmen karir. Penelitian ini memberikan implikasi bagi semua institusi yang ingin meningkatkan person–organization fit dan komitmen karyawannya. Implikasi ini membantu institusi untuk mengambil inisiatif khusus untuk meningkatkan person job fit bagi para dosennya, yang selanjutnya akan meningkatkan tingkat komitmen dosennya untuk tetap bertahan di institusinya.